Optimalisasi Limbah Daun Cengkeh Kering (Syzygium aromaticum) sebagai Repelan Alami Ramah Lingkungan: Optimization of Dried Clove Leaf Waste (Syzygium aromaticum) as an Environmentally Friendly Natural Repellant - Putra, Zidhandika Nagita; Nugraheni, Yudhi Ratna; Prastowo, Joko; Ariyadi, Bambang; Awaludin, Aan (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2025)
Munggang Wetan hamlet is one of the clove-producing areas in Kulon Progo, located in the Menoreh mountain plateau. These areas have the potential to spread malaria. The clove plant has insecticidal compounds that can be used as a mosquito repellent. Dried clove leaves are still considered waste that has not been utilized by the community. The purpose of this community service is to transfer knowledge to the people of Munggang Wetan hamlet in utilizing clove leaf waste as a natural mosquito repellent. The method used was counseling and practical. The extraction process of clove leaf waste for repellant uses the maceration method and utilizes 96% Ethanol as a solvent. The result of this activity was that the training participants were able to understand and make mosquito repellant by utilizing clove leaf waste and packaging it in spray bottles. Natural mosquito repellant derived from the extraction of clove leaf waste with 96% ethanol solvent can be used by the community and has effective work as a natural mosquito repellent.